Timely initiation of breastfeeding and associated factors among mothers with vaginal and cesarean deliveries in public hospitals of Addis Ababa, Ethiopia - Mekonnen, Adane; Shewangizaw, Zewdu (Clinical Journal of Obstetrics and Gynecology, 2022)
Background: WHO and UNICEF recommend breastfeeding to be initiated within an hour of birth. However, timely initiation of breastfeeding remains low in Ethiopia. Therefore, this study aimed to compare the timely initiation of breastfeeding and associated factors with cesarean and vaginal deliveries in public hospitals in Addis Ababa, 2021. Methods and materials: Comparative cross-sectional study was conducted from January 2021 to February 2021 in public hospitals of Addis Ababa. 322 mothers within three days of delivery at the postnatal ward of the respective public hospitals were selected. A multi-stage sampling method was employed with the final participants being recruited by systematic random sampling. Data was entered to Epi data Version 4.6 and analysis was performed by SPSS Version 26. A Binary and multivariate logistic regression statistical model was used. Adjusted odds ratio with 95% CI was computed to see the strength of association. Result: Timely breastfeeding initiation was 79 (51.2%) and 123 (80%) for cesarean and vaginal deliveries. With a vaginal delivery, pre-lacteal feeding (AOR = 5.50, 95% CI: 1.83 - 16.57) was significantly associated with timely initiation of breastfeeding. Multiparity (AOR = 2.14, 95% CI: 1.02 - 4.50), support from health care workers (AOR = 2.602, 95% CI: 1.16 - 5.82), and pre-lacteal feeding (AOR = 2.55, 95% CI: 1.13 - 5.75) were significantly associated with timely initiation of breastfeeding with cesarean delivery. Conclusion: The rate of timely initiation of breastfeeding differs according to the mode of delivery. Cesarean delivery, as compared to vaginal delivery, was associated with a lower rate of timely initiation of breastfeeding.